# the original problem was: Solve: sin(3x)-sin(x)=cos(2x) so far i've gooten to: sin(x)(2sin(x)cos(x)-1)=cos^2(x)-sin^2(x) Where would I go from here related homework questions

• #### It’s review question, I need this as soon as possible. Thank you 3) For thè diferential equation: (a) The point zo =-1 is an ordinary point. Compute the recursion formula for the coefficients of...

It’s review question, I need this as soon as possible. Thank you 3) For thè diferential equation: (a) The point zo =-1 is an ordinary point. Compute the recursion formula for the coefficients of the power series solution centered at zo- -1 and use it to compute the first th...

• #### the original problem was: Solve: sin(3x)-sin(x)=cos(2x) so far i've gooten to: sin(x)(2sin(x)cos(x)-1)=cos^2(x)-sin^2(x) Where would I go from here

the original problem was:Solve: sin(3x)-sin(x)=cos(2x)so far i've gooten to:sin(x)(2sin(x)cos(x)-1)=cos^2(x)-sin^2(x)Where would I go from here?

• #### Dont copié formé thé book oh ya dont copié formé thé book cause you Oiil inde up being triste soi remembré not toi copié frome thé book oh ya

Dont copié formé thé book oh ya dont copié formé thé book cause you Oiil inde up being triste soi remembré not toi copié frome thé book oh ya!translation in english please!

• #### the original problem was: Solve: sin(3x)-sin(x)=cos(2x) so far i've gotten to: sin(x)(2sin(x)cos(x)-1)=cos^2(x)-sin^2(x) Where would I go from here

the original problem was: Solve: sin(3x)-sin(x)=cos(2x) so far i've gotten to: sin(x)(2sin(x)cos(x)-1)=cos^2(x)-sin^2(x) Where would I go from here?

• #### Prove: sin2x / 1 - cos2x = cotx My Attempt: LS: = 2sinxcosx / - 1 - (1 - 2sin^2x) = 2sinxcosx / - 1 + 2sin^2x = cosx / sinx - 1 = cosx / sinx - 1/1 = cosx / sinx - sinx / sinx -- Prove: 2sin(x+y)sin(x-y) = cos2y - cos2x My Attempt: RS: = 1 - 2sin^2

Prove:sin2x / 1 - cos2x = cotxMy Attempt:LS:= 2sinxcosx / - 1 - (1 - 2sin^2x)= 2sinxcosx / - 1 + 2sin^2x= cosx / sinx - 1= cosx / sinx - 1/1= cosx / sinx - sinx / sinx--Prove:2sin(x+y)sin(x-y) = cos2y - cos2xMy Attempt:RS:= 1 - 2sin^2y - 1 - 2sin^2x= 1 - 1 - 2sin^2y - 2sin^2x= -2...

• #### Find sin(x/2) if sin(x)= -0.4 and 3pi/2 < or equal to (x) < or equal to 2pi Let's use cos 2A = 1 - 2sin<sup>2</sup> A and we can match cos x = 1 - 2sin<sup>2</sup> (x/2) so we will need cos x we know sin x = -

Find sin(x/2) if sin(x)= -0.4 and 3pi/2 < or equal to (x) < or equal to 2piLet's use cos 2A = 1 - 2sin2 A and we can match cos x = 1 - 2sin2 (x/2) so we will need cos x we know sin x = -.4 and x is in the fourth quadrant, so the cosine will be positive. Drawing a right angl...

• #### 2) Use the sum and difference identites sin[x + pi/4] + sin[x-pi/4] = -1 sinx cospi/4 + cosxsin pi/4 + sinx cos pi/4 - cosx sin pi/4 = -1 2 sin x cos pi/4 =-1 cos pi/4 = sqr2/2 2sin^x(sqrt2/2) = -1 sin x = -sqrt2 x = 7pi/4 and 5pi/4 Am I co

2) Use the sum and difference identites sin[x + pi/4] + sin[x-pi/4] = -1 sinx cospi/4 + cosxsin pi/4 + sinx cos pi/4 - cosx sin pi/4 = -1 2 sin x cos pi/4 =-1 cos pi/4 = sqr2/2 2sin^x(sqrt2/2) = -1 sin x = -sqrt2 x = 7pi/4 and 5pi/4 Am I correct?

• #### cos(tan + cot) = csc only simplify one side to equal csc so far I got this far: [((cos)(sin))/(cos)] + [((cos)(cos))/(sin)] = csc I don't know what to do next

cos(tan + cot) = csconly simplify one side to equal cscso far I got this far: [((cos)(sin))/(cos)] + [((cos)(cos))/(sin)] = cscI don't know what to do next

• #### the original problem was: (sin x + cos x)^2 + (sin x - cos x)^2 = 2 steps too please I got 1 for (sin x + cos x)^2 but then what does (sin x - cos x)^2 become since it's minus

the original problem was: (sin x + cos x)^2 + (sin x - cos x)^2 = 2steps too pleaseI got 1 for (sin x + cos x)^2 but then what does (sin x - cos x)^2 become since it's minus?

• #### 2. A dragon is flying around in a pattern given by the parametric curve r(t) (cos(t) cos((sin(t) sin(t) cos(t)j. cos(t) - cos sin(t)-sin(t) cos(t))j (a) Find a formula for the velocity of the dragon...

2. A dragon is flying around in a pattern given by the parametric curve r(t) (cos(t) cos((sin(t) sin(t) cos(t)j. cos(t) - cos sin(t)-sin(t) cos(t))j (a) Find a formula for the velocity of the dragon at time t (b) Find all the times at which the dragon's speed is zero. Explai...

• #### The only ideas that can be used include: area ABCI-RA2(A+B+C-lpi), the Pythagorean theorem: Cos c cos a cos b. Vectors-dot product cross product, sin A-sin a/sin c; cos A-cos a sin b/sin c; spher...

The only ideas that can be used include: area ABCI-RA2(A+B+C-lpi), the Pythagorean theorem: Cos c cos a cos b. Vectors-dot product cross product, sin A-sin a/sin c; cos A-cos a sin b/sin c; spherical law of sines, spherical law of cosines for sides and spherical law of cosin...

• #### Solve the following equation for 0 less than and/or equal to "x" less than and/or equal to 360 -- cos^2x - 1 = sin^2x -- Attempt: cos^2x - 1 - sin^2x = 0 cos^2x - 1 - (1 - cos^2x) = 0 cos^2x - 1 - 1 + cos^2x = 0 2cos^2x - 2 = 0 (2cos^2x/2)= (-2/2) cos^

Solve the following equation for 0 less than and/or equal to "x" less than and/or equal to 360--cos^2x - 1 = sin^2x--Attempt:cos^2x - 1 - sin^2x = 0cos^2x - 1 - (1 - cos^2x) = 0cos^2x - 1 - 1 + cos^2x = 02cos^2x - 2 = 0(2cos^2x/2)= (-2/2)cos^2x = -1cosx = square root of -1And I c...

Need Online Homework Help?

Get FREE HOMEWORK EXPERT